2020
DOI: 10.1016/j.heliyon.2020.e03286
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of an indirect air cooling system combined with evaporative cooling

Abstract: This study developed an indirect air-cooling combined with evaporative cooling (IAC þ EC) system for temporary storage of fruit and vegetables (FV) to improve the shelf life of fresh produce under hot and humid climatic conditions. The aim of the study was to investigate the effect of IAC þ EC in providing optimum storage environment of temperature and relative humidity (RH) for the tomato fruit compared to storage under ambient conditions. The IAC þ EC system had a 53-m 3 storage chamber able to store 3.8 ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…Temperature is a crucial factor required to maintain optimum conditions during the storage of fresh produce (Sibanda & Workneh, 2020a). Figure 4a–c illustrates the linear effect of Vnormala, mnormalw, and tcp on air temperature drop (TD).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature is a crucial factor required to maintain optimum conditions during the storage of fresh produce (Sibanda & Workneh, 2020a). Figure 4a–c illustrates the linear effect of Vnormala, mnormalw, and tcp on air temperature drop (TD).…”
Section: Resultsmentioning
confidence: 99%
“…RH is another important factor in maintaining optimum conditions while storing fresh produce (Chavan et al, 2021; Sibanda & Workneh, 2020a). The impact of each input factor on the rise of air RH is shown in Figure 6a–c.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the challenges such as modes of heat transfer, physics of vapor formation during vibrations in case of automobiles, established heat transfer and heat flux predictive capability needs to be accounted for use of these systems in automobile applications. Sibanda et al [4] have studied the indirect air cooling along with the evaporative cooling in tomato fruit for temporary storage under the conditions of hot and humidity. They measured the temperature and RH (Using psychometric unit) hourly during a period of 28 days.…”
Section: Introductionmentioning
confidence: 99%
“…The tomatoes stored under IAC+EC showed higher firmness and hue angle, maintained lower concentration of sugars, had lower physiological weight loss and improved shelflife and marketability as compared to ambient conditions. Sibanda and Workneh (2020) tested the performance of such a system and it provided storage conditions of temperature of 15.7 to 16.4°C and relative humidity of 89.6 to 93.8%. Both studies provided the efficacy of the system except the energy requirements.…”
Section: Introductionmentioning
confidence: 99%